Cassia fistula L as an antifungal agent and 7 hydroxyflavone from Cassia fistula as antifungal principle - Padma Chatterjee, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Cassia fistula L as an antifungal agent and 7 hydroxyflavone from Cassia fistula as antifungal principle